Change Management and Organization Efficiency in Federal Radio Corporation of Nigeria - Ugo Chuks Okolie; R. Godspower Akpoyibo (Jurnal Transparansi Publik (JTP), 2025)
This study explored the effect of change management on organizational efficiency in Federal Radio Corporation of Nigeria (FRCN) Benin City, Edo State. The study adopted a descriptive research design and was anchored on complexity theory. Questionnaire was administered to respondents and the analysis was based on the retuned questionnaire. The findings revealed that there was a positive and significant relationship between change management and organizational efficiency. The study also showed that change management had positive impact on organizational efficiency in Federal Radio Corporation of Nigeria (FRCN) Benin City, Edo State. Therefore, study concluded that organizational change comes with different challenges and it can significantly disrupt expectations about important issues or events and as such there is a significant relationship between organizational change management and organizational efficiency. The study recommended among others that management of Federal Radio Corporation of Nigeria (FRCN) Benin City, Edo State should ensure effective communication link between management and workers before any change process is embarked upon to attract co-operation from workers and to stifle any doubts, fears or resistance to change. This will go a long way to enhance organizational efficiency.